Diaspora and development: the case of Mauritius. Issue 6 (18th August 2021) - Ramtohul, Ramola
ABSTRACT: This paper explores the different prospects offered by diasporic connections towards development in the island of Mauritius. Mauritius maintains strong diasporic connections with the homelands of the "ancestral" diasporas of its multi-ethnic population. The contribution and assistance of these countries towards the development of Mauritius at multiple levels has been significant and is still ongoing. However, the connection between the Mauritian diaspora and Mauritius as a homeland is so far less solid. The paper explores the two dimensions of diaspora in terms of their contribution to development, arguing that Mauritius needs to do more towards reaching out to its diaspora.